Macroeconomic factors and oil price influence stock market return in Malaysia / Normah Salehuddin - Salehuddin, Normah (Faculty of Business and Management, 2015)
This project paper title “Macroeconomic Factors and Oil Price Influence Stock Market Return in Malaysia” is conducted as a part of the requirement needed by the faculty of Business Management, University Teknologi Mara (UiTM). The purpose of this study is to investigate the relationship between the macroeconomic factors and oil price volatility towards the stock market return in Malaysia. This study aims to examine the relationship between oil price volatility and macroeconomic variables such as real interest rate, real exchange rate, inflation rate and financial crisis that influence stock market return in Malaysia. This study is using quarterly data from 1995 to 2015.Moreover, this study employed Ordinary Least Square model to examine the regression model. Researcher chose to use time series data method to conduct this study and survey in order to obtain the data. Data used in this research are secondary data such as journals and articles, books, internet, and e-resources from UiTM data stream. The result obtained shows that the oil price and macroeconomic factors are significant and positively related with stock market return in Malaysia. The researcher also provides some recommendations and suggestion to help the future researcher after analysis, findings and interpretation data is done.